Acute paroxysmal cold haemoglobinuria; a case report and literature review (Bangladesh Journal of Medical Science, 2021)
Paroxysmal cold hemoglobinuria (PCH) is a very rare subtype of autoimmune hemolytic anemia caused by the presence of cold-reacting autoantibodies in the blood and characterized by the sudden presence of hemoglobinuria, typically after exposure to cold temperatures. The acute onset PCH occurs following viral illnesses whilst the chronic form is secondary to hematological malignancies and tertiary syphilis. It is a complement mediated intravascular hemolytic anemia associated with a biphasic antibody against the P antigen on red cells. We describe a three year child who had acute onset PCH following likely viral infection. The diagnosis was confirmed by demonstration of strongly positive Donnath Landsteiner antibodies. She made a gradual recovery with supportive treatment, ten days following the initial detection of haemolysis. Parents were educated about the need to avoid cold exposure to prevent precipitation of further haemolysis and folic acid was commenced to assist the recovery of erythropoiesis.Bangladesh Journal of Medical Science Vol.20(3) 2021 p.654-657